Implementasi Metode Resitasi Dalam Meningkatkan Evaluasi Belajar Siswa Pelajaran Sejarah Kelas XI IPS MA Al-Huda Kediri - Devi Ayu Widyaningrum; Dita Hendriani (Universitas 45 Surabaya, 2024)
Educators strive for learning methods to improve the results of their students' learning evaluations at the end of material testing. The results of learning evaluations by students can be used as a benchmark for educators in assessing how well students understand the learning material that has been taught and can see the realization of learning objectives. History itself is a field of study that is rich in material. The use of the recitation method has an essential role in increasing students' understanding. This research examines the success of applying the recitation method to history learning in an effort to improve student learning outcomes. By using pre-test and post-test research, we will find out the differences before and after implementing the recitation method. These findings indicate that the integration of recitation methods in history learning can support increasing the academic achievement of students in the field of history.